2015
DOI: 10.1039/c4ra13060j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an EDOT-based polymer: optoelectronic properties and electrochromic device application

Abstract: Spectroelectrochemistry graph of a novel TPA/DTD electrochromic device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Moreover, Figure 2b shows the two bands at positive potentials of + 0.85, + 1.2 V and at negative of À0.50 V vs Ag/Ag + , which corresponds to the radical cation (polaronic), dication (bipolaronic) and radical anion states of pDAE, respectively. [30,31] Moreover, an operational stability of pDAE was investigated upon repetitive cycling between the oxidized and reduced states and integrating the area of cycling voltammograms, which corresponds to the electric current passed in one cycle. The increase in current density with each consecutive cycle is attributed to the formation pDAE on the surface of ITO electrode.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Figure 2b shows the two bands at positive potentials of + 0.85, + 1.2 V and at negative of À0.50 V vs Ag/Ag + , which corresponds to the radical cation (polaronic), dication (bipolaronic) and radical anion states of pDAE, respectively. [30,31] Moreover, an operational stability of pDAE was investigated upon repetitive cycling between the oxidized and reduced states and integrating the area of cycling voltammograms, which corresponds to the electric current passed in one cycle. The increase in current density with each consecutive cycle is attributed to the formation pDAE on the surface of ITO electrode.…”
Section: Synthesismentioning
confidence: 99%
“…When the peak current values in the graph of cyclic voltammetry are plotted versus the scan rates, linearity of the graph exhibits that the polymer adheres well to the electrode surface and the electrochemical processes are not controlled by the diffusion rate of the electrolyte (inset graph in the Figure 2c). [30,31] Moreover, an operational stability of pDAE was investigated upon repetitive cycling between the oxidized and reduced states and integrating the area of cycling voltammograms, which corresponds to the electric current passed in one cycle. [32,33] It was observed that the polymer maintains both an electrochemical activity and electrochromic behaviour, yet 28 percent decrease in passed electric charge after the 500 switching cycles as depicted in Figure 2d, indicates relatively poor operational stability and a tendency to degrade.…”
Section: Synthesismentioning
confidence: 99%
“…EC materials exhibit electrochemical effect where an electroactive material undergoes redox reaction, and thus there is a reversible color change upon applying a low DC voltage. [16][17] Therefore, EC materials control the amount of light passing through windows, so-called EC windows, smart windows or smart glass. A smart glass should meet these requirements: when the glass is transparent, it should have a high optical transmittance.…”
Section: Introductionmentioning
confidence: 99%
“…because of their highly π-conjugated polymeric chains and metal like conductivity [1]- [4]. The optical properties of conducting polymers [5]- [7] are as important as electrical properties because they allow number of applications such as sensing [8]- [10], displays and other opto-electronic applications [11] [12]. Along with various advantages, these pristine conducting polymers have several drawbacks such as poor emission, processability and stability.…”
Section: Introductionmentioning
confidence: 99%